STRATEGI PUBLIC RELATION PT KAI DAOP 8 SURABAYA DALAM MEMPERTAHANKAN CITRA MELALUI COMMUNITY RELATION (STUDI KASUS PADA RAILFANS) (Universitas Negeri Surabaya, 2023)
The corporation is currently considering controlling an image, this image aims to maintain the existence of the company. KAI is a large company, therefore image control is also very necessary. The image of PT KAI Daop 8 Surabaya is handled by the public relations division. PT KAI Daop 8's public relations has several strategies to maintain its image. One of the public relations programs to maintain its image is a community relations program by cooperating with railfans. This research is descriptive qualitative research with a case study method and uses a constructivist paradigm, namely a paradigm that sees social conditions as a systematic analysis. Data collection was obtained from the results of in-depth interviews with several informants who match the criteria. The results of this study indicate that the community relations strategy that collaborates with Railfans has the same background, namely wanting to introduce trains to the whole community, therefore PT KAI Daop 8 Surabaya and Railfans have a strong bond. In the community relations strategy, there are several fields in it to support an image of PT KAI Daop 8 Surabaya, namely Community Branding, Community Gathering, Community Development, Socialization, Social Service, and Public Service. PT KAI, which acts as a partner for railfans, really supports all the positive things that are done by railfans so that as a community, railfans have very high loyalty too